Towards a contextualised conceptualisation of social justice for post-apartheid Namibia with reference to Allan Boesak's framing of justice - Kasera, Basilius M. (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.